(untitled) (Indian Journal of Nematology, 2024)
Out of 15 populations of Meloidogyne graminicola collected from different parts of India, four populations namely, Bhubaneswar (Odisha), Kalyani (West Bengal), Jorhat (Assam) and Vellayani (Kerala), showed the incidence of P. penetrans. Bhubaneswar isolate of P. penetrans (MgPp) was selected for further studies. In the host range studies on MgPp, no endospore attachment was observed on Heterodera avenae, H. cajani, H. zeae, Tylenchulus semipenetrans and Aphelenchoides sp. but spore encumbrance was recorded on J2 of Meloidogyne javanica, M. incognita, besides M. graminicola. MgPp completed its life cycle and sporefilledn females were observed on all the three species of Meloidogyne. Comparison of the life cycle of the two strains of P. penetrans, i.e., MgPp on M. graminicola and another isolate (MjPp) on M. javanica, revealed that although M. graminicola adult females were formed by 16th day, mature endospores of MgPp were formed only by 24th day; while M. javanica adult females were formed by 24th day and MjPp reached mature spore stage by 28th day. The sequence of developmental stages of P. penetrans was similar in both the strains. The life cycles of respective nematode species and P. penetrans strains were synchronized. Morphological comparison was made on the spores of MgPp and MjPp by light microscopy and SEM. The endospore of MgPp was larger compared to MjPp, however, sporangium was bigger in MjPp. SEM observations, however, could not resolve any differences in the endospore as well as sporangium measurements.